Video Monitoring Application using Wireless Sensor Node with Various External Antenna - Amerrul Zabri; Mohamad Kamal A. Rahim; Farid Zubir; Norsaidah Muhamad Nadzir; Huda A. Majid (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Surveillance and monitoring has become very important for security reasons these days. The use of wireless sensor node device offers a variety of platform depends on the attached sensor. When an image sensor is attached, the wireless sensor node is capable of monitoring an area wirelessly. Since wireless environment uses antenna to transmit and receive data, antenna is an important component that affects the video monitoring performance. This paper describes a surveillance system using Raspberry Pi with various external antenna. The Raspberry Pi with Pi Camera module and various types of antennas was used for testing and experimentation in line-of-sight (LOS) and non-line-of-sight (NLOS) condition. The results revealed that the Yagi Uda antenna gives the best output in terms of its signal strength and average Receive (Rx) rate.